THE MODERATING ROLE OF SELF-CONTROL ON THE INFLUENCE OF PRODUCT QUALITY AND DISCOUNT PROMOTION ON BUYING DECISION OF HALAL COSMETICS ON E-COMMERCE - Nadyah Zubdatun Nihayati; Nur Asnawi; Nihayatu Aslamatis Solekah (Adisam Publisher, 2026)
This study aims to analyze the influence of product quality and discount promotions, as well as the moderating role of self-control on halal consumers’ purchasing decisions within the e-commerce ecosystem. The widespread implementation of aggressive digital marketing strategies frequently triggers impulsive consumption behavior, thereby necessitating a deeper examination of how the internal characteristics of Muslim consumers are capable of mitigating such external stimuli. A quantitative approach was employed in this research involving 250 Muslim respondents who were active users of seven leading halal cosmetic brands. Primary data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software. The findings reveal that halal product quality and discount promotions exert positive and significant direct effects on purchasing decisions. Furthermore, this study demonstrates that self-control significantly functions as a negative moderator, weakening the influence of discount promotions on purchasing decisions. These results indicate that the stronger the self-control possessed by Muslim consumers, the lower their sensitivity toward the temptation of price discounts, thereby ensuring that purchasing activities remain within the boundaries of actual needs (al-hajat). The implications of this study emphasize the importance for halal cosmetic industry practitioners to shift from price-based marketing strategies toward value-based marketing approaches that prioritize product quality integrity and ethical consumption values.